EVALUASI LITERATUR TERHADAP PENGARUH GAME-BASED LEARNING DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA - Prananda, Gingga; Judijanto, Loso; Stavinibelia; Aristanto; Ramadhona, Rossa; Lestari, Nana Citrawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this literature study research is to evaluate the effect of Game-based learning (GBL) in improving students' learning motivation by analyzing the concept of GBL, reviewing relevant motivation theories, and assessing findings from previous studies on the impact of GBL on students' learning motivation. This type of research is a literature study. Literature study is a research method that aims to collect, analyze, and interpret various sources of information relevant to the topic or problem being studied. Game-based learning (GBL) is an educational approach that integrates game elements to create interactive and enjoyable learning experiences, increasing student engagement and motivation. This concept includes the use of game mechanisms such as challenges, points, and rewards to support educational goals, and can be applied in both digital and non-digital formats. GBL has the potential to improve learning motivation by reducing boredom, increasing intrinsic and extrinsic motivation, and strengthening social and cooperation skills. GBL success factors include effective game design, curriculum compliance, active teacher involvement, availability of quality technology, and student engagement with constructive feedback.